(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This study investigates how border tensions between China and India have affected the economic relationship and the political partnership between these two countries over the last 50 years. China and India have been at odds over their borders since the initial establishment of the McMahon line in 1914. Since the Indo-China War in 1962, mistrust and disputes regarding the actual border have reigned, seemingly affecting the relationship at all levels. In spite of enduring political tensions, an economic relationship has blossomed to the point that China is now India’s largest trading partner. While bilateral trade is expected to top US60 billion in 2010-11 ending March 31, according to latest official estimates, and is likely to continue to increase, the border issue remains virtually unchanged from 50 years ago. Although economically lucrative Indo-Chinarelations are riper for competition than cooperation, theborder dispute has become increasingly problematic for both parties.